THU0491 Genome-Wide Transcriptional Profiling of Isolated Immune Cell Populations from SLE Patients with Different Ancestral Backgrounds. (10th June 2014) - Sharma, S.; JIn, Z.; Rosenzweig, E.; Rao, S.; Ko, K.; Niewold, T.B.
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex multi-system autoimmune disease of uncertain etiology. Patients from different ancestral backgrounds demonstrate differences in clinical manifestations and autoantibody profiles. Objectives: In this study we examined genome-wide transcriptional patterns in major immune cell subsets across different ancestral backgrounds. Methods: Peripheral blood was collected and run on 208 Illumina HumanHT-12 V4 expression BeadChip arrays. Subjects included 21 African-American (AA) and 21 European-American (EA) SLE patients, 5 AA and 5 EA controls. CD4 + T-cells, CD8 + T-cells, monocytes and B cells were purified by flow sorting. Each cell subset from each subject was run on a separate array. Differentially expressed genes (DEGs) were determined by comparing cases and controls of the same ancestral background. Results: The overlap in DEG lists between different cell types from the same ancestral background was very modest (<1%). Typically between 5-10% of DEGs were shared when comparing the same cell type between different ancestral backgrounds. Global IFN-stimulated gene (ISG) expression revealed that AA subjects demonstrated more concordance across all studied cell types. Two subgroups of patients were identified based on the ISG expression profiles. One subgroup showed higher ISGs expression in all cell types, and the other subgroup had higher ISG expression only in T and B lymphocytes but not in monocytes. Conclusions: We find striking differences in gene expression between different immune cell subsets and between ancestral backgrounds in SLE patients. The IFN signature is diverse, with different transcripts represented in different cell populations, and signature-positive cell subsets differed in EA vs. AA patients. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5291